Ketamine Usage Effectivity on Treatment-Resistant Depression Diagnosed Patients: a Scoping Review - Nugroho, Satrio Wahyu; Agustina Konginan; Gadis Meinar Sari; Erikavitri Yulianti (Faculty of Medicine, Universitas Airlangga, 2024)
Introductions: In Indonesia, a median of 6.1% of people diagnosed with depression disorder are people over 15 years old. Only 9% of that amount underwent medical treatment, while the rest, 91%, did not undergo treatment for their depressive conditions. Inadequate and inappropriate treatment of depression will lead to Treatment-Resistant Depression (TRD). Using ketamine as a pharmacotherapy opens up new possibilities for TRD treatments. Methods: This study uses a retrospective observational study design with a systematic review approach, in which all variable data were collected from previous studies aimed at measuring the effectiveness of ketamine pharmacological therapy in patients diagnosed with treatment-resistant depression (TRD) using placebo as a benchmark of the effectiveness of ketamine in reduced clinical symptoms of TRD using secondary data in the form of study results and analyzes from published studies of the effectiveness of ketamine therapy. Results: Administration of ketamine at doses of 0.4 mg/kg and 0.5 mg/kg is more effective as an antidepressant compared to placebo in adults and is effective in the elderly at doses above 0.2 mg/kg with a maximal effect at 24 hours post-administration and disappeared by about 7 days post-administration. Conclusions: The administration of ketamine therapy is more effective at reducing depressive symptoms in diagnosed patients (TRD) than the use of placebo and repeated administration of ketamine can increase the likelihood that TRD sufferers respond to therapy and experience remission.